End vertices in containment interval graphs - Alcón, Liliana Graciela (2017)
An interval containment model of a graph maps vertices into intervals of a line in such a way that two vertices are adjacent if and only if the corresponding intervals are comparable under the inclusion relation. Graphs admitting an interval containment model are called containment interval graphs or CI graphs for short. A vertex v of a CI graph G is an end-vertex if there is an interval containment model of G in which the left endpoint of the interval corresponding to v is less than all other endpoints. In this work,we present a characterization of end-vertices in terms of forbidden induced subgraphs.